Producción de bioetanol a partir de los desechos lignocelulosicos industriales del asparagus officinalis l. - Millones Reaño, Enrique Jonathan (2011)
The aim of this thesis was to make the production of bioethanol from lignocellulosic waste "peladilla" Asparagus offwinalis "asparagus" using Candida utilis var. .major CECT 1430. This proceeded to perform the pre-treatment of peladilla asparagus by chemical, physical and physicochemical methods. Subsequently, we proceeded to perform the extraction of Total Reducing Sugars "ART", determining a maximum concentration of 7 g / L with which the fermentation broth was established. Before starting the fermentation process, a bioreactor of 16 cm stirred tank with Rushton turbine and proceeded to the preparation of the inoculum from the Candida strain utilis var major CECT 1430. The culture medium was formulated was constructed from dilutions of total reducing sugars from 7.0 to 0.85 g / L. The bioprocess was carried out at 25 ° C, at pH 4.0 to 4.5 and for a time of 72 hours; After this time proceeded to determine the percentage of ethanol. It was found that single cell protein and ethanol percentage increase progressively from 0.13 to 1.80 g / L and from 0.40 to 2.04%, respectively, as the concentration of "ART" from asparagus peladilla increases. It is concluded that the production of bioethanol increases as the concentration of "ART" from peladilla. Furthermore, optimal performance of C. utilis var. corresponding to 91.66%) Major is obtained 1.75 g concentration / L decreases as the concentration of reducing sugars increases. The highest value in the production of bioethanol 2.04% is equivalent to 20.4 ml of ethanol and at a concentration of 7 g / L A.R.T. "of" peladilla "of Asparagus officinalis." Stud ".